2018
DOI: 10.3389/fmicb.2018.00760
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of the Toxic Effects of the Production of Lycopene and Its Precursors

Abstract: Using cells as microbial factories enables highly specific production of chemicals with many advantages over chemical syntheses. A number of exciting new applications of this approach are in the area of precision metabolic engineering, which focuses on improving the specificity of target production. In recent work, we have used precision metabolic engineering to design lycopene-producing Escherichia coli for use as a low-cost diagnostic biosensor. To increase precursor availability and thus the rate of lycopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The data matrix file obtained from LC-MRM/MS was used as input to perform statistical analysis by using online tool MetaboAnalyst 1 (Xia et al, 2012). The original data obtained were normalized to OD 600 equivalent of the number of cells at the time of harvesting post stress (OD s ) (Miguez et al, 2018) Normalization for paired comparison was performed using the following calculation [Normalized metabolite peak area for Control Experiment = (P c /OD c ) X OD s ], where P is peak area. The normalization parameters are given in Supplementary Table S11.…”
Section: Methodsmentioning
confidence: 99%
“…The data matrix file obtained from LC-MRM/MS was used as input to perform statistical analysis by using online tool MetaboAnalyst 1 (Xia et al, 2012). The original data obtained were normalized to OD 600 equivalent of the number of cells at the time of harvesting post stress (OD s ) (Miguez et al, 2018) Normalization for paired comparison was performed using the following calculation [Normalized metabolite peak area for Control Experiment = (P c /OD c ) X OD s ], where P is peak area. The normalization parameters are given in Supplementary Table S11.…”
Section: Methodsmentioning
confidence: 99%
“…As an example, Miguez et al. used silylation agents to study small polar metabolites from the lycopene and mevalonate pathways of E. coli [70]. Among these, homocysteine and homoserine have been identified as possible growth inhibitors associated with the overnight induction of the mevalonate pathway of E. coli .…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…Further, they validated that the intermediate homocysteine could contribute to the growth inhibition and the antagonistic effect between the mevalonate and lycopene pathways, resulting in the homocysteine-induced toxicity in lycopene production. This work indicated that metabolomics would be beneficial to reveal the mechanisms of the metabolite toxicity, and subsequently help to improve the metabolic engineering for the biosynthesis of carotenoid [37].…”
Section: Metabolic Engineering Of the Heterogeneous Mva Pathwaymentioning
confidence: 98%